Public EV charging infrastructure - why charging behaviours matter for placement, ownership and operations? - Trivikram Dokka; Sonali SenGupta; Aaditya Bhardwaj (Queen's University Belfast, Queen's Management School, 2022)
Sustainable uptake of electric vehicles will require efficient provision of public electric vehicle charging infrastructure for which it is essential to understand plug-in behaviors of electric vehicle users. Using plug-in data from 19 public charging stations and amenities in Durham, clustering, coupled with quantile regression analysis was used. Instead of focusing on the conditional average, we explain the effects of various factors, including availability of other amenities, on the entire distribution of the plug-in duration. Results show that both demand for charging and other amenities surrounding the charging station play an important role. More specifically, these effects are different at different quantiles of plug-in distribution.
Keywords: 330